Detection of 15 bursts from the fast radio burst 180916.J0158+65 with the upgraded Giant Metrewave Radio Telescope. (26th September 2020) - Marthi, V R; Gautam, T; Li, D Z; Lin, H-H; Main, R A; Naidu, A; Pen, U-L; Wharton, R S
ABSTRACT: We report the findings of an upgraded Giant Metrewave Radio Telescope (uGMRT) observing campaign for FRB 180916.J0158+65, which was recently found to show a 16.35-d periodicity of its active cycle. We observed the source at 550–750 MHz for ∼2 h during each of three successive cycles at the peak of its expected active period. We find 0, 12 and 3 bursts, respectively, implying a highly variable bursting rate even within the active phase. We consistently detect faint bursts with spectral energies only an order of magnitude higher than the Galactic burst source SGR 1935+2154. The times of arrival of the detected bursts rule out many possible aliased solutions, strengthening the findings of the 16.35-d periodicity. A periodicity search over a short time-scale returned no highly significant candidates. Two of the beamformer-detected bursts were bright enough to be clearly detected in the imaging data, achieving subarcsec localization, and proving to be a proof-of-concept for FRB imaging with the GMRT. We provide a 3σ upper limit of the persistent radio flux density at 650 MHz of 66 μJy, which, combined with the European VLBI Network and Very Large Array limits at 1.6 GHz, further constrains any potential radio counterpart. These results demonstrate the power of the uGMRT for providing targeted observations to detect and localize known repeating FRBs.